Critical Review and Simulation of Mid-range Wireless Power Transfer for Electronic Device - Tan S.Y.; Lee H.J. (Institute of Physics Publishing, 2023)
Electric fields; Energy transfer; Green computing; Magnetic resonance; Magnetism; CST microwave studio; Electronic device; Green environments; Magnetic resonance couplings; Resonance-magnetic; Surface current; Transmitter and receiver; Wireless power transfer; Inductive power transmission